2021
DOI: 10.3390/ijms22115475
|View full text |Cite
|
Sign up to set email alerts
|

Activated STAT3 Is a Novel Regulator of the XRCC1 Promoter and Selectively Increases XRCC1 Protein Levels in Triple Negative Breast Cancer

Abstract: Base Excision Repair (BER) addresses base lesions and abasic sites induced by exogenous and endogenous stressors. X-ray cross complementing group 1 (XRCC1) functions as a scaffold protein in BER and single-strand break repair (SSBR), facilitating and coordinating repair through its interaction with a host of critical repair proteins. Alterations of XRCC1 protein and gene expression levels are observed in many cancers, including colorectal, ovarian, and breast cancer. While increases in the expression level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 63 publications
3
17
0
1
Order By: Relevance
“…STAT3 activation following high glucose exposure has been documented in numerous cell lines [27,28]. We also found that STAT3 serves as an inducible regulator of XRCC1 in the non-tumorigenic human embryonic kidney cell lines HEK293T [3]. However, no links between increased glucose concentrations, the activation of STAT3, and increased XRCC1 and DNA repair have been made.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…STAT3 activation following high glucose exposure has been documented in numerous cell lines [27,28]. We also found that STAT3 serves as an inducible regulator of XRCC1 in the non-tumorigenic human embryonic kidney cell lines HEK293T [3]. However, no links between increased glucose concentrations, the activation of STAT3, and increased XRCC1 and DNA repair have been made.…”
Section: Introductionmentioning
confidence: 75%
“…To examine the high glucose regulation of XRCC1, we exposed cells to 30 mM glucose for up to 24 h. We selected the osteosarcoma cell line U2OS, which has high STAT3 activation, and HEK293T, which we showed previously has an inducible STAT3 response [3]. HEK293T cells were grown in 25 mM glucose (basal glucose (BG)), and the U2OS cells were grown in 11 mM (BG).…”
Section: Acute High Glucose Stimulates Activation Of Stat3 and Xrcc1 ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ответ на ХТ может быть обусловлен активностью систем репарации ДНК, в частности, системы эксцизионной репарации оснований (BER) или нуклеотидов (NER). Интегральным белком BER, координирующим сборку всего белкового комплекса репарации, является XRCC1, который кодируется геном XRCC1 [2]. Система репарации NER и изменения в ней, в частности, однонуклеотидные полиморфизмы, также играют важную роль в ответе на цитотоксическую терапию [3].…”
Section: Introductionunclassified